2019
DOI: 10.1111/cei.13391
|View full text |Cite
|
Sign up to set email alerts
|

Circulating β cell-specific CD8+ T cells restricted by high-risk HLA class I molecules show antigen experience in children with and at risk of type 1 diabetes

Abstract: Summary In type 1 diabetes (T1D), autoreactive cytotoxic CD8+ T cells are implicated in the destruction of insulin‐producing β cells. The HLA‐B*3906 and HLA‐A*2402 class I genes confer increased risk and promote early disease onset, suggesting that CD8+ T cells that recognize peptides presented by these class I molecules on pancreatic β cells play a pivotal role in the autoimmune response. We examined the frequency and phenotype of circulating preproinsulin (PPI)‐specific and insulin B (InsB)‐specific CD8+ T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 98 publications
3
15
1
Order By: Relevance
“…This finding is consistent with previous studies stipulating that the HLA locus is the strongest risk allele in the development of IBM 10 . HLA alleles are known to be associated with a variety of autoimmune diseases, such as systemic lupus erythematosus (SLE), 11 type 1 diabetes mellitus 12 and rheumatoid arthritis(RA) 13 . The genes products in this region play a fundamental role in the immune response.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous studies stipulating that the HLA locus is the strongest risk allele in the development of IBM 10 . HLA alleles are known to be associated with a variety of autoimmune diseases, such as systemic lupus erythematosus (SLE), 11 type 1 diabetes mellitus 12 and rheumatoid arthritis(RA) 13 . The genes products in this region play a fundamental role in the immune response.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, in recent onset cases, different islets harbored different reactivities, which could reflect different stages of the autoimmune process. More recently, a high proportion of preproinsulin (PPI) specific cells have been detected in the islets of donors with T1D (17,18), confirming previous data obtained from blood samples and highlighting the role of PPI as one of the most prominent antigens in disease pathogenesis (15,(19)(20)(21)(22). Attempts to detect neoantigens in situ have not been reported so far but are on the horizon.…”
Section: The Evolving Understanding Of the Pathogenesis Of Human T1dsupporting
confidence: 77%
“…In addition, their potential role in sustaining the effector functions of CD8+ T-cells should not be neglected (14). Both CD4+ and CD8+ Tcell populations decline with beta-cell loss, suggesting that their presence is driven by a beta-cell antigen (11,12,15). However, the exact role infiltrating T-cells play in the pathogenesis of the disease remains to be determined both in terms of specificity and function.…”
Section: The Evolving Understanding Of the Pathogenesis Of Human T1dmentioning
confidence: 99%
“…On the other hand, other studies demonstrated no significant differences between T1D and control individuals in the frequencies of circulating CD8 T cells reactive to multiple A*02:01-restricted beta-cell epitopes (PPI 14 (3,4,6,10). However, beta cell-specific CD8 T cells are more differentiated in patients with newly diagnosed T1D compared to healthy controls (6), and memory T cell subsets were enriched within PPI 5-12 -specific CD8 T cell populations in HLA-B*39:06 + children with newly diagnosed T1D, but not in healthy control subjects (10). Overall, these studies suggest that phenotypic subset analysis of such circulating autoreactive T cells could help to identify patients with T1D.…”
Section: Mini-review What Distinguishes T1d Patients From Healthy Indmentioning
confidence: 95%